Lipid and lipoprotein profile changes in newborn calves in response to the perinatal period - Arfuso Francesca (Sciendo, 2017)
The aim of this study was to evaluate the dynamic changes of serum lipid and lipoprotein profiles in 6 newborn calves during the first five days of life. From each calve blood sampling was performed daily starting from day 1 (after colostrum intake) until day 5 of life. Blood samples collected from each animal were tested for serum total lipids, phospholipids, non-esterified fatty acids (NEFAs), triglycerides, very low density lipoproteins (VLDLs), total cholesterol (Total-Chol), high density lipoproteins (HDLs) and low density lipoproteins (LDLs). One-way repeated measures analysis of variance (ANOVA) was applied to determine the effect of days of life on the studied parameters in calves. A statistically significant effect of days of life was found on all serum lipid and lipoprotein indices measured in calves with the exception of NEFAs that showed unchanged values throughout the monitoring period. The changes observed in calves during the early postnatal period are most likely due to the transition in energy sources, from a maternal nutrient supply comprising mainly carbohydrates and amino acids to the colostrum and milk diet rich in fat.